2006
DOI: 10.1021/jf060022q
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxygenase from Banana Leaf:  Purification and Characterization of an Enzyme That Catalyzes Linoleic Acid Oxygenation at the 9-Position

Abstract: The objective of the present study was to purify and characterize the lipoxygenase (LOX) from banana leaf (Giant Cavendishii, AAA), an unutilized bioresource. LOX was extracted, isolated, and purified 327-fold using 25-50% saturation of ammonium sulfate fractionation, hydroxyapatite column separation, and gel filtration on Superdex 200. The molecular mass of the purified LOX was 85 kDa, K(m) was 0.15 mM, and V(max) was 2.4 microM/min.mg using linoleic acid as substrate. Triton X-100 was required in the extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 36 publications
4
29
0
Order By: Relevance
“…The K m value of purified opium poppy LOX determined using linoleic acid as a substrate was similar to the K m value of soluble LOX from tomato fruits (Suurmeijer et al, 1998). The K m value of LOX from pea seeds was 0.44 mM (Szymanowska et al, 2009) and was 0.15 mM in LOX purified from banana leaves (Kuo et al, 2006) and soluble LOX from chicory (Daglia et al, 2005). Other plant LOXs display K m values in the lower micromolar range (Fornaroli et al, 1999;Lorenzi et al, 2006;Sellhorn et al, 2011).…”
Section: Kinetic Study and The Effect Of Calcium Ion Concentration Onsupporting
confidence: 53%
“…The K m value of purified opium poppy LOX determined using linoleic acid as a substrate was similar to the K m value of soluble LOX from tomato fruits (Suurmeijer et al, 1998). The K m value of LOX from pea seeds was 0.44 mM (Szymanowska et al, 2009) and was 0.15 mM in LOX purified from banana leaves (Kuo et al, 2006) and soluble LOX from chicory (Daglia et al, 2005). Other plant LOXs display K m values in the lower micromolar range (Fornaroli et al, 1999;Lorenzi et al, 2006;Sellhorn et al, 2011).…”
Section: Kinetic Study and The Effect Of Calcium Ion Concentration Onsupporting
confidence: 53%
“…The monomeric nature of LOX was in accordance with LOX extracted from germinating barley (Yang et al 1993), durum wheat endosperm (Hsieh and McDonald, 1984), ungerminating barley (Peter et al 1991), wheat germ (Shiiba et al 1991), durum wheat semolina (Barone et al 1999), tomato (Catherine et al 1998), Cichorium intybus (Daglia et al 2005), rice (Ratachatachaiyos and Theerakulkait, 2009) and Pleurotus ostreatus (Abdullah et al 2014). The molecular mass of purified LOX from banana leaf was 85 kDa (Kuo et al 2006). According to Babitha et al (2004), LOX isozymes in pearl millet seedlings had molecular mass 83, 77 and 73 kDa for LOX 1, 3 and 6, respectively.…”
Section: Molecular Massmentioning
confidence: 99%
“…Biogeneration of aldehydes and alcohols used in the flavor industry can be carried out naturally through enzymatic pathways utilizing enzymes such as lipase, alcohol dehydrogenase (ADH), lipooxygenase (LOX), hydroperoxide lyase (HPLS) (Gigot et al 2010). Kuo et al (2006) reported that banana leaves (Musa cv. Cavendish) contains a membrane-bound enzyme of 9-LOX, which is able to produce oolong tea-like, melonlike, and fruity cucumber-like flavor upon pickling or when treated with soybean oil, linoleic acid, linolenic acid and respectively; the kinetic properties were comparable to LOX obtained from canola seed and English pea.…”
Section: Biogeneration Of Flavormentioning
confidence: 99%
“…Numerous studies have been done to improve the usage of banana by-products to meet the escalating demand of raw materials supply in various industries (Clarke et al 2008;Doran et al 2005;Emaga et al 2008a;Kuo et al 2006). These researches paved new and alternative ways in creating new products and applications with value added approach at the cost of recycling banana agricultural wastes.…”
Section: Introductionmentioning
confidence: 99%